Employee Retention Factors: The Case of Hotels in Cape Town, South Africa - Ezeuduji, Ikechukwu O; Mbane, Thandokazi Lulu (Journal of Economics and Behavioral Studies, 2017)
High turnover of employees in the hotel sector has been widely reported in academic papers. This high turnover has associated costs, such as financial costs, inconsistency in delivering service quality, and probable loss of customer loyalty. This empirical study investigates hotel employees’ responses to statements that relate to work conditions that support employee retention. Selected three, four and five star hotels in Cape Town, South Africa participated in this study. A structured respondent-completed questionnaire was used to collect data that were subjected to descriptive, bivariate and multivariate analyses. Result highlights suggest that hotel employees, dominated by the female population, are mostly not so desperate to leave their employment soon, however not many of them have worked in the hotel for more than five years. There are positive inter-correlations among ‘employee retention’ factor and other factors that relate to work conditions that support employee retention (compensation, employee development, work engagement, work relations, and working hours). Results also show that ‘strict supervision’, ‘long working hours’ and ‘perceived unfair salary’ are the top major concerns for hotel employees. These findings will enable hotel employers address employee concerns in order to curb the high employee turnover costs. Possible comparative research in other nations and continents will help establish cultural similarities and differences among nations or continents.